EVIDENCE-BASED DROWNING AND INJURY PREVENTION: COASTAL PUBLIC SAFETY AT HOT WATER BEACH AND PAKIRI BEACH. (7th October 2012) - Mulcahy, N; Sullivan, B
Abstract : Background: Surf Life Saving New Zealand developed a risk assessment programme to help the water safety sector identify high risk locations and resource them accordingly. To date, assessments have been conducted at 110 beaches and recommendations implemented at two sites, Hot Water Beach and Pakiri Beach. Aims/Objectives/Purpose: This programme aims to reduce the incidence of drowning and injury by sharing with decision-makers the most effective safety interventions for a particular site, and encouraging efficient use of limited resources. Methods: The risk assessments involved the identification of hazards, extraction of information from stakeholders and accumulation of supporting data (eg, incident data). Data was analysed and risk mitigation plans formulated. Stakeholders were brought together to discuss the plans and assist with their implementation. Collaboration has been essential to the programme's success. Results/Outcomes: Various safety interventions were implemented at the sites, including the installation of safety signage and emergency phones, extension of surf lifeguarding services and targeted education. Initial data indicates the evidence-based approach is having a significant impact. The sites will be monitored over the next decade. Significance/Contribution to the Field: An evidence-based approach to drowning and injury prevention is essential to understand why people continue to drown, and to develop effective risk mitigation. Historically drowning prevention initiatives have been 'one size fits all'; this programmes site-specific strategy is an innovative approach to drowning prevention.